IT Project Management Critical Success Factors - Trigo, António (2020)
IT Project Management Critical Success Factors (CSFs) are the areas of an Information Technology (IT) project that are essential to its success, and that must be identified and followed throughout the life cycle of the project. The identification, definition and communication of CSFs help to ensure that the project manager and team maintain the focus on what is important while avoiding spending resources on other less important areas. Although each IT project is unique and therefore has a unique set of CFSs, in this article, we propose a framework based on a literature review, whose results provide researchers and project managers with a comprehensive understanding of current CSFs of IT projects.